Patent Review (2017-2020) of the Keap1/Nrf2 Pathway Using PatSeer Pro: Focus on Autoimmune Diseases - Dionysios V. Chartoumpekis; Chun-Yan Fu; Panos G. Ziros; Gerasimos P. Sykiotis (MDPI AG, 2020)
Research on the antioxidant pathway comprising the transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) and its cytoplasmic inhibitor Kelch-like ECH-associated protein 1 (Keap1) is ever increasing. As modulators of this pathway have started to be used in clinical trials and clinical practice, Nrf2 has become the subject of several patents. To assess the patent landscape of the last three years on Nrf2 and evaluate the main fields they refer to, we used the web-based tool PatSeer Pro to identify patents mentioning the Nrf2 pathway between January 2017 and May 2020. This search resulted in 509 unique patents that focus on topics such as autoimmune, neurodegenerative, liver, kidney, and lung diseases and refer to modulators (mainly activators) of the Nrf2 pathway as potential treatments. Autoimmunity emerged as the main theme among the topics of Nrf2 patents, including a broad range of diseases, such as systemic sclerosis, systemic lupus erythematosus, multiple sclerosis, inflammatory bowel diseases, Hashimoto's thyroiditis, etc.; however, there was a dearth of experimental support for the respective patents' claims. Given that chronic inflammation is the main element of the pathophysiology of most autoimmune diseases, the majority of patents referring to activation of Nrf2 as a method to treat autoimmune diseases base their claims on the well-established anti-inflammatory role of Nrf2. In conclusion, there is strong interest in securing intellectual property rights relating to the potential use of Nrf2 pathway activators in a variety of diseases, and this trend parallels the rise in related research publications. However, in the case of autoimmunity, more research is warranted to support the potential beneficial effects of Nrf2 modulation in each disease.